PENANGANAN BANJIR DAERAH ALIRAN SUNGAI BABON KOTA SEMARANG - Ikhwanudin, ikhwanudin; Yudaningrum, Farida; Wardani, Agustina (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
Floods are natural disasters that we often encounter during the rainy season. Apart from there are also tidal floods which are caused by global warming, this problem occurs in the city of Semarang, especially North Semarang, specifically the north coast of the Java Sea. Floods that occurred in 2021 in the city of Semarang include Starting from Genuk, Kaligawe, Satsiun Tawang, Tanjungmas, Karangayu, the flood disaster was caused by high rainfall, while tidal floods caused high tides and inundated roads and houses of residents on the north coast of Semarang city. To handle this problem, the government Currently we have made embankments, namely making embankments including the Sringin River which is equipped with a ponpa, Tenggang River, Babon River, Semarang River, Banger River, and others. These embankments are equipped with pumps so that when the water from upstream to downstream is high, the water is pumped. to the sea, the aim is to find out one of the annual discharges of the river, namely the Babon, and to find out the tamping capacity of the Babon River Longstorage. Apart from that, there is a method for handling tidal floods, namely using the Babon River Longstorage which is equipped with a pump, if there is high tide which inundates roads and houses. residents then the pump is turned on, whereas if the water recedes and does not inundate residential areas then the pump is turned off. Flood control analysis is calculated using the HEC-RAS program simulation using a return period of 50 years. Based on calculations using the HEC-HMS program. The flood discharge is 2,529 m3/sec. The high tide elevation is + 1.67 m, while the normal water level is -0.5 m.